(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines effective strategies for teaching pedagogy to young learners, focusing on approaches that enhance engagement, understanding, and application of pedagogical concepts. By integrating interactive activities, collaborative learning, and culturally responsive practices, educators can foster a deeper connection to educational principles among young students. The article outlines specific techniques, such as play-based learning, storytelling, and inquiry-based projects, providing practical recommendations for educators to implement in their classrooms. The findings underscore the importance of creating a supportive and inclusive learning environment where young learners can develop essential pedagogical skills in preparation for their future educational journeys.